2021
DOI: 10.35699/1983-3652.2022.36032
|View full text |Cite
|
Sign up to set email alerts
|

Autopercepción inicial y nivel de competencia digital del profesorado universitario

Abstract: El profesorado en nuestro contexto educativo se ha visto sumergido por los avances tecnológicos, provocando cambios en sus funciones, gestión académica y comunicación, convirtiéndose en guías, mediadores, facilitadores y motivadores de procesos de aprendizajes significativos y relevantes. Dicha situación refleja la importancia que asume en la actualidad la competencia digital docente. En el presente artículo se presenta un estudio realizado al profesorado de la Universidad de Cádiz, que tiene como objetivos co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
(10 reference statements)
1
3
0
2
Order By: Relevance
“…From the results found, it is observed that teachers' competence levels are located between the level of integrator (B1) and expert (B2), as in the research by Barragán, et. al (2021), Boté-Vericad, et.…”
Section: Discussionsupporting
confidence: 54%
“…From the results found, it is observed that teachers' competence levels are located between the level of integrator (B1) and expert (B2), as in the research by Barragán, et. al (2021), Boté-Vericad, et.…”
Section: Discussionsupporting
confidence: 54%
“…In the case of the second variable that has been studied, the daily amount of time using technology in the teaching profession, there are also similar studies as the one carried out by Barragán-Sánchez et al [11], which show that the level of digital competence does not correspond with the amount of time using technology in the classroom.…”
mentioning
confidence: 66%
“…Finally, the pilot experience can increase and lead institutions regarding the strategies to follow in order to establish strategies for teacher training in digital competences for teachers. In this sense, the present study offers the possibility of looking at the training environment as a training plan that, thanks to its architecture, is offered for teacher training through a training offer of different levels linked to the European Framework for Digital Competence in Education: DigCompEdu [37].…”
Section: Discussionmentioning
confidence: 99%